Economic Mobility in Vietnam in the 1990s - Glewwe, Paul; Nguyen, Phong (World Bank, Washington, D.C., 2013)
Vietnam's high economic growth in the 1990s led to sharp reductions in poverty, yet over the same time period inequality increased. This increased inequality may be less worrisome if Vietnamese households experience a high degree of income mobility over time. This is because high mobility implies that the long-run distribution of income is more equally distributed than the short-run distribution, since some individuals or households are poor in some years, while others are poor in other years. The authors examine economic mobility in Vietnam using recent household survey panel data. The problem of measurement error in the income variable, which exaggerates the degree of economic mobility, is directly addressed. Correcting for measurement error dramatically changes the results. At least one half of measured mobility is because of measurement error.